PENGEMBANGAN REAKTOR FOTOKATALITIK FILM TITANIA UNTUK PENGOLAHAN AIR GAMBUT MENJADI AIR BERSIH - Gusfiyesi Gusfiyesi; Randi Permana Putra; Rizki Alfi; Dartini Dartini (JURNAL ILMIAH TEKNOLOGI INDSUTRI (SAINTI), 2018)
The photocatalytic of Titania is an alternative solution for treating peat water into clean water that corresponding to the quality standard of clean water. A photocatalytic reactor of Titania has been developed to obtain more optimum peat water treatment efficiency. The optimum composition of the titania suspension to be coated into the titania film on the surface of the photocatalytic reactor is on the composition of titania and the starch in water with the ratio of (4: 1: 25) wt.%, and durability enhanced by adding the ACR dispersant. Titania film obtained by screen printing coating technique. The batch system of photocatalytic reactor with a 1 L / 6 hour reactor capacity has been developed into a continuous photocatalytic solar reactor with a fivefold capacity of batch system. The reactor will be developed again into a peat water treatment technology of household-scale industry that can produce 100 L of clean water from peat water for six hours at a cost of less than Rp 1000, -.